Effects of Nigella sativa oil and thymoquinone on radiation-induced oxidative stress in kidney tissue of rats - ALKIŞ, HİLAL (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2021)
Ionizing radiation leads to release of free radicals into the systemic circulation from irradiated tissues. These free radicals cause oxidative stress in distant organs. Oxidative status may be reversed by naturally occurring antioxidant agents. The aim of this study was to investigate protective and antioxidant effects of Nigella sativa oil (NSO) and thymoquinone (TQ) in kidney tissue of rats exposed to cranial irradiation. Forty-eight SpragueDawley rats were divided into six groups: IR group received irradiation (IR) to total cranium plus saline; IR plus NSO group received IR and NSO; IR plus TQ group received IR and TQ; sham group did not receive NSO, TQ or IR; control group of TQ received dimethyl sulfoxide; control group of NSO received saline. Total oxidant status (TOS), oxidative stress index (OSI) and lipid hydroperoxide (LOOH) levels were studied as oxidative parameters, and total antioxidant status (TAS), total sulfhydryl levels, paraoxonase (PON), ceruloplasmin (Cp) and arylesterase activities were determined as antioxidative parameters in the kidney tissue of rats. Kidney TOS, OSI and LOOH levels were significantly lower in IR plus TQ, IR plus NSO and sham groups compared to IR group (p < 0.001). TAS, PON and Cp activities in IR group were significantly lower compared to the control group (p < 0.001). PON and Cp activities were significantly higher in IR plus NSO and IR plus TQ groups compared to IR group (p < 0.001). In conclusion, free radicals generated by cranial ionizing radiation exposure cause oxidative stress in kidney. NSO and TQ exhibit protective and antioxidant effects against oxidative damage in rats.
Keywords: Free radicals; Nigella sativa oil; Thymoquinone; Ionizing radiation; Kidney; ISCHEMIA-REPERFUSION INJURY; DAMAGE; ARYLESTERASE; LIPOPOLYSACCHARIDE; PARAOXONASE; IMPAIRMENT; GENERATION; LEVEL; WOMEN; LIVER